Respostas
respondido por:
6
Olá,
(2m-6)·x²+6x+3 = 0
Para ser do primeiro grau (2m-6) = 0
2m-6 = 0
2m = 6
m = 6/2
m = 3
Assim, a equação fica da seguinte maneira:
(2m-6)·x²+6x+3 = 0
(2(3)-6)·x²+6x+3 = 0
(6-6)·x²+6x+3 = 0
0·x²+6x+3 = 0
0+6x+3 = 0
6x+3 = 0 ⇒ equação do 1º grau
Resposta:
m = 3
(2m-6)·x²+6x+3 = 0
Para ser do primeiro grau (2m-6) = 0
2m-6 = 0
2m = 6
m = 6/2
m = 3
Assim, a equação fica da seguinte maneira:
(2m-6)·x²+6x+3 = 0
(2(3)-6)·x²+6x+3 = 0
(6-6)·x²+6x+3 = 0
0·x²+6x+3 = 0
0+6x+3 = 0
6x+3 = 0 ⇒ equação do 1º grau
Resposta:
m = 3
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás